Une solidarité en mouvement : figures de la militance féministe québécoise - Sandrine Ricci; Mélissa Blais; Francine Descarries (Amnis)
This article examines the question of feminist commitment in 21st century Quebec. It looks at the ways workers in the Quebec women's movement (MFQ) relate to activism in light of the evolution of the movement over time and of the conceptual frameworks that cross it. More specifically, it introduces the figure of the "professional feminist activist" which now represents a key figure in the landscape of Quebec activism following the institutionalization of the women's movement. We are focusing on the activist path of three of these MFQ actors to highlight the various relationships to activism that the figure of the professional feminist activist comprises, taking into account their inclusion in the social and historical continuity as well as in feminist theory.